Tata Rias dan Tata Busana Tari Milok Sambatan Karya Raden Gunawan di Banyuasin III: Penelitian - Mevia; Rully Rochayati; Deria Sepdwiko (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Milok Sambatan Dance is a creative dance in Banyuasin which was created in 2003 in Banyuasin precisely in Pangkalan Balai, which tells about the joy of Banyuasin children when helping their parents in the rice fields by working together. Milok Sambatan means milu bergotong royong or working together. The research method used is a qualitative descriptive method. The results of the study showed that the Milok Sambatan dance tells of solidarity between the Banyuasin people in working together. And in the makeup of the Milok Sambatan dance, it is a simple or unobtrusive makeup and the clothes used are also fairly simple dance clothes that are adjusted to the dance, namely people working in the rice fields.